Spesifikasi Tafsir dari Masa Sahabat hingga Masa Modern - Hanna Salsabila (Jurnal Penelitian Ilmu Ushuluddin, 2023)
Efforts to dig up information about the history of the development of interpretation in terms of periodization, from the time of the Companions to the modern period is part of the aim of the discourse on the science of the Qur'an and interpretation. Then, the method used in this research is qualitative through literature study using a historical approach. This study describes the interpretation of the companion period, the tabi'in period and the modern period. This study concludes that there are differences in the development of interpretation in each period. The characteristic of the interpretation of the Companions period is that it does not interpret all verses and its interpretation is concise. The characteristics of the interpretations of the tabi'in period are the many interpretations that contain information from the scribes, there is fanaticism of the schools of thought, there are several tabi'in who only take interpretations from the desired companions. The hallmark of modern interpretation is interpretation which is linked to the social conditions of people's lives. This research provides constructive aspirations regarding the study of the science of the Qur'an and interpretation which is focused on the historical aspects of its development along with the figures of commentators according to their periodization.